2013
DOI: 10.1016/j.cardfail.2013.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker-Guided Therapies in Heart Failure: A Forum for Unified Strategies

Abstract: The complexity of standard medical treatment for heart failure is growing, and such therapy typically involves 5 or more different medications. Given these pressures, there is increasing interest in harnessing cardiovascular biomarkers for clinical application to more effectively guide diagnosis, risk stratification, and therapy. It may be possible to realize an era of personalized medicine for heart failure treatment in which therapy is optimized and costs are controlled. The direct mechanistic coupling of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…In other words, if COMPANION had been conducted in a generalized HFrEF population without the lengthened QRS inclusion criterion, it almost certainly would have produced negative results. Enrichment of clinical trial populations through the use of biomarkers thatidentify responsive subpopulations is something that is highly desirable but difficult to attain(44), and COMPANION and CARE-HF demonstrate that this approach can be successful.…”
mentioning
confidence: 98%
“…In other words, if COMPANION had been conducted in a generalized HFrEF population without the lengthened QRS inclusion criterion, it almost certainly would have produced negative results. Enrichment of clinical trial populations through the use of biomarkers thatidentify responsive subpopulations is something that is highly desirable but difficult to attain(44), and COMPANION and CARE-HF demonstrate that this approach can be successful.…”
mentioning
confidence: 98%
“…GWAS studies and other large population studies along with enhanced mechanisms to analyze genetic data are critical for the progression of pharmacogenomics. However, many challenges still remain in applying pharmacogenetics to the clinical practice in heart failure management, and the clinical utility of pharmacogenetic testing in cardiovascular patients still remains elusive (30). Physicians and cardiologists will need to understand, communicate, and manage this new genomic information to provide the patient with appropriate education and management recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…All six studies showed mortality benefit in the BNP-guided therapy group compared to controls and no studies reported increased incidence of adverse effects in this group (74). Therefore eventually it may be possible to use a combination of pharmacogenetics and biomarker levels to guide HF therapy, which could further optimise the therapeutic benefit (75). Investigation into the proteomics of HF may also reveal variation that can be used to guide HF therapy hand-in-hand with biomarkers and pharmacogenomics, which would facilitate bridging the gap of genotype and phenotype.…”
Section: Non-genetic Factors Influencing Drug Tailoring In Heart Failurementioning
confidence: 97%